Gender dan Perilaku Memilih: Sebuah Kajian Psikologi Politik - Rahmaturrizqi, Rahmaturrizqi; Nisa, Choirun; Nuqul, Fathul Lubabin (Universitas Negeri Surabaya, 2012)
There are interesting developments of political psychology, particularly in the effort of women in politics arena. Until the mid-year 2007, at least 82 women were recorded following the elections in 232 provincial-level regions and districts level. Out of the above, 26 women (30.76%) registered as a candidate for the leader of region and 57 women (69.24%), registered as a deputy leader of the region, although only eight women who are successfully elected as the leader of region and 11 elected as deputy leaders of regional (Arifin, 2008). With direct elections as happened today, making the candidates should follow the